OSCILLATOR temporality FACTORS implementation of innovative activity of economic entities - P. Gureev (Вестник университета)
Presents arguments justifying the need of accounting for temporary (temporal) factor in the management of innovation. Given modern interpretation of the innovation process from the standpoint of transdisciplinary scientific approach. The proposed mechanism of formation of the oscillator susceptibility of the entity to innovate.